ChemInform Abstract: A New Quinoline‐Based Acylhydrazone for Highly Selective Fluorescence Recognition of Cu(II) and Sulfide in Aqueous Solution. Issue 52 (24th December 2013) - Tang, Lijun; Zhou, Pei; Qi, Zhikai; Huang, Zhenlong; Zhao, Jia; Cai, Mingjun
Abstract The title fluorescent compound (III) shows high selectivity to Cu2+ ("ON‐OFF" behavior) and the generated (III)‐Cu2+ complex exhibits excellent selectivity to sulfide ions ("OFF‐ON" behavior).